Presence of methyl paraben in anti-diabetic herbal preparations (Journal of the Asiatic Society of Bangladesh, Science, 2023)
Plant-based hypoglycemic therapeutics have been increasing in consumption due to the escalation of type 2 diabetes and its related complications. However, the safety of the preparations is little understood. Parabens (alkyl esters of p-hydroxybenzoic acid) are widely used as preservatives in these pharmaceuticals. However, the presence of methylparaben in formulations raises anxiety due to its potential endocrine disruption functions. Endocrine disruption could lead to undesirable health abnormalities and carcinogenic, estrogenic, and adverse reproductive effects. The present investigation directs toward estimating of methylparaben in some anti-diabetic herbal preparations using UV- Vis spectrophotometric method abiding by International Conference on Harmonization (ICH) guidelines for validation. The analytical wavelength of methylparaben in methanol was determined and found at 256.5 nm. The method obeys Beer’s law in the analytical range and has a good coefficient of determination (r2= 0.9881). The limit of detection (LOD) and limit of quantification (LOQ) were 0.19 ppm and 0.57 ppm, respectively. Recoveries were 91.3-98.8% in analyte-free plant matrix and 91-105.8 % in a diluent. The coefficient of variation (CV%) varied between 0.005- 0.268% for different standards. Results of forty-eight anti-diabetic herbal preparations showed methylparaben was detected in thirty-four samples in the range of 13.12 – 325.13 mg/day with a mean exposure value of 78.25 mg/day. However, none of the samples raise concerns about safety (the safety ceiling for paraben is 420 mg/day). More investigation is required to determine, whether the herbal drugs are safe to consume in terms of methylparaben.J. Asiat. Soc. Bangladesh, Sci. 48(1-2): 41-52, June-December 2022